2012
DOI: 10.1073/pnas.1121214109
|View full text |Cite
|
Sign up to set email alerts
|

Role of histone deacetylases in transcription factor regulation and cell cycle modulation in endothelial cells in response to disturbed flow

Abstract: Vascular endothelial cells (ECs) are exposed to different flow patterns (i.e., disturbed vs. laminar), and the associated oscillatory shear stress (OSS) or pulsatile shear stress (PSS) lead to differential responses. We investigated the roles of class I and II histone deacetylases (HDAC-1/2/3 and HDAC-5/7, respectively) in regulating NF-E2-related factor-2 (Nrf2) and Krüppel-like factor-2 (KLF2), two transcription factors governing many shear-responsive genes, and the cell cycle in ECs in response to OSS. Appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
123
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 24 publications
10
123
0
Order By: Relevance
“…In the present study, we have demonstrated that KLF-2 is involved in the context of shear-eliciting RARα/miR-10a/ GATA6/VCAM-1 signaling in ECs. In combination with previous results (6,19), our findings advance the notion that PS can induce not only the dissociation of HDAC-5/7 from MEF2 to increase KLF-2 expression, but also the accumulation of RARα and RXRα and their association in EC nuclei to enhance RARα-RARE binding and miR-10a expression, thereby down-regulating GATA6 and VCAM-1 in ECs (Fig. 6).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the present study, we have demonstrated that KLF-2 is involved in the context of shear-eliciting RARα/miR-10a/ GATA6/VCAM-1 signaling in ECs. In combination with previous results (6,19), our findings advance the notion that PS can induce not only the dissociation of HDAC-5/7 from MEF2 to increase KLF-2 expression, but also the accumulation of RARα and RXRα and their association in EC nuclei to enhance RARα-RARE binding and miR-10a expression, thereby down-regulating GATA6 and VCAM-1 in ECs (Fig. 6).…”
Section: Discussionsupporting
confidence: 74%
“…5G). Our previous study showed high levels of HDACs in ECs in the inner curvature of the AA, but not in the outer curvature of the AA and the TA (6). Taken together, these in vivo results are in agreement with our in vitro findings indicating that EC expression levels of RARα, RXRα, HDACs, miR-10a, GATA6, and VCAM-1 are flow patternspecific to induce proinflammatory and anti-inflammatory responses under OS and PS, respectively.…”
Section: Ps Induction Of Mir-10a Is Regulated By Increased Expressionsupporting
confidence: 81%
See 1 more Smart Citation
“…For instance, nuclear factor-like 2 activation by LSS induced the expression of several antioxidative genes, such as heme oxygenase 1 and NAD(P)H quinone oxidoreductase 1, involving phase II detoxification (25,26). In contrast, OSS inhibited nuclear factor-like 2 activity by deacetylation, resulting in decreased expression of heme oxygenase 1 (27). In addition to PXR, constitutive androstane receptor, another xenobiotic nuclear receptor, is also expressed in ECs (28).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Lee et al 65 have elegantly demonstrated that exposure of HUVEC to OS induces the expression of both class I and II histone deacetylases (HDACs) and their nuclear accumulation in a PI3K/Akt-dependent manner, whereas pulsatile US induced phosphorylation-dependent nuclear export of class II HDACs. Moreover, OS induced the association of HDAC-1/2/3 with Nrf2 and the association of HDAC-3/5/7 with myocyte enhancer factor-2, leading to diminished expression of NQO1 and the transcription factor Klf2.…”
Section: Hypertensionmentioning
confidence: 99%